“Defund the police:”: perceptions among protesters in the 2020 March on Washington - Cobbina-Dungy, Jennifer (Criminology & public policy, 2022)
Using qualitative interviews, this study examines how protesters with varying levels of commitment to the Black Lives Matter movement perceive the slogan defund the police. Findings indicate while a small number had reservations regarding the term, the vast majority of protesters associate defunding as a two-step process that starts with reduction of police budgets, followed by reallocation of these resources toward much needed services in the very communities the departments serve. Findings also revealed prior engagement with the Black Lives Matter movement, and the level of commitment of participants did play an important role in being able to provide nuanced context to the call for action.